Noncompetitive Expansion of Cytotoxic T Lymphocytes Specific for Different Antigens during Bacterial Infection - Vijh, Sujata (American Society for Microbiology, 1999)
Listeria monocytogenes is an intracellular bacterium that elicits complex cytotoxic T-lymphocyte (CTL) responses in infected mice. The responses of CTL populations that differ in antigen specificity range in magnitude from large, dominant responses to small, subdominant responses. To test the hypothesis that dominant T-cell responses inhibit subdominant responses, we eliminated the two dominant epitopes of L. monocytogenes by anchor residue mutagenesis and measured the T-cell responses to the remaining subdominant epitopes. Surprisingly, the loss of dominant T-cell responses did not enhance subdominant responses. While mice immunized with bacteria lacking dominant epitopes developed L. monocytogenes-specific immunity, their ability to respond to dominant epitopes upon rechallenge with wild-type bacteria was markedly diminished. Recall responses in mice immunized with wild-type or epitope-deficient L. monocytogenes showed that antigen presentation during recall infection is sufficient for activating memory cells yet insufficient for optimal priming of naive T lymphocytes. Our findings suggest that T-cell priming to different epitopes during L. monocytogenes infection is not competitive. Rather, T-cell populations specific for different antigens but the same pathogen expand independently.